P21 Is it syphilis? the dark art of interpreting syphilis serology. (18th May 2015) - Patel, Hemanti; Alexander, Sarah; Fifer, Helen
Abstract : Background/introduction: The diagnosis of syphilis relies mainly upon a panel of serological tests. A sensitive treponemal test such as the enzyme immunoassay (EIA) is used as a screening test; another treponemal test such as the Treponema pallidum particle agglutination (TPPA) assay is used to confirm a reactive screening test. Difficulties arise when these tests produce a discordant result. Our laboratory uses the INNO-LIA immunoblot assay to resolve discordant screening results. Aim(s)/objectives: To evaluate whether the use of the INNO-LIA enables clinically useful interpretation. Methods: We reviewed the last 100 INNO-LIA tests performed by our laboratory. Results: Comparison of EIA, TPPA and INNO-LIA results are shown in Table 1. The Antibody Index is a measure of the positive signal in the EIA (≥1.2 is a positive result). Discussion/conclusion: In EIA positive (AI ≥5)/TPPA equivocal cases the INNO-LIA was always positive or equivocal, consistent with treponemal infection. The INNO-LIA test may be unnecessary in these cases. In EIA positive/TPPA negative cases, the INNO-LIA is able to resolve the discordant result less than half of the time. Overall the INNO-LIA produced equivocal results in 44% of serums, which is unsatisfactory for confirming the diagnosis of syphilis. Although the INNO-LIA does help resolve some cases, there remains a need for new diagnostics.